2021
DOI: 10.1200/op.21.00270
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Stage Is Associated With Exceeding Target Price in the Oncology Care Model

Abstract: PURPOSE: To explore mean difference between Oncology Care Model (OCM) total costs and target price among breast cancer episodes by stage under the Centers for Medicare and Medicaid Services OCM payment methodology. METHODS: Breast cancer episodes from OCM performance period 1-4 reconciliation reports (July 1, 2016-July 1, 2018) were linked with health record data from a large, academic medical center. Demographics, total cost of care (TCOC), and target price were measured by stage. Adjusted differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Patients with metastatic disease had nearly 8 more encounters per year compared with patients with early-stage breast cancer. This higher encounter complexity with higher stage parallels prior financial studies demonstrating that increasing breast cancer stage and triple negative status are associated with increasing overall costs of care, 23,24 and that patients with metastatic breast cancer have the highest total cost of care and greatest likelihood of exceeding target price in Oncology Care Models 23 . Put into the context of these studies, our data suggest that future value-based models must adjust for various tumor and treatment characteristics, particularly breast cancer stage, such that these models accurately reflect overall complexity of encounter volume and provider effort.…”
Section: Discussionmentioning
confidence: 64%
“…Patients with metastatic disease had nearly 8 more encounters per year compared with patients with early-stage breast cancer. This higher encounter complexity with higher stage parallels prior financial studies demonstrating that increasing breast cancer stage and triple negative status are associated with increasing overall costs of care, 23,24 and that patients with metastatic breast cancer have the highest total cost of care and greatest likelihood of exceeding target price in Oncology Care Models 23 . Put into the context of these studies, our data suggest that future value-based models must adjust for various tumor and treatment characteristics, particularly breast cancer stage, such that these models accurately reflect overall complexity of encounter volume and provider effort.…”
Section: Discussionmentioning
confidence: 64%
“…Thirty-six (68%) of our included studies reported costs for early-stage cancer [ 19 , 20 , 22 , 24 27 , 29 31 , 34 40 , 44 48 , 53 58 , 60 62 , 65 67 , 70 , 71 ]; 17 (32%) included metastatic cancer [ 20 23 , 25 , 27 , 30 , 33 , 36 , 38 40 , 50 , 53 , 60 , 68 , 70 ]; 12 (23%) included both early and metastatic cancer [ 20 , 22 , 25 , 27 , 30 , 36 , 38 40 , 53 , 60 , 70 ]; for 12 (23%), the cancer stage was not reported [ 28 , 32 , 41 43 , 49 , 51 , 52 , 59 , 63 , 64 , 69 ]. Generally, across our included studies, metastatic breast cancer was associated with higher costs than earlier stage cancer (see Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Breast cancer stage is an important predictor of costs: previous studies have shown the amount and intensity of treatment tends to be higher at more advanced than earlier stages [ 8 , 9 ]. Our identified studies generally suggested that metastatic (Stage IV) cancer was more costly than early (Stage I–III) cancer [ 20 , 22 , 25 , 27 , 30 , 36 , 38 40 , 53 , 60 , 70 ]. However, it is important to recognise the heterogeneous nature of these costing studies and that our suggestion comes particularly from the range of costs rather than the median across cost estimates and studies; although the three identified studies by Brezden-Masley et al [ 38 40 ] greatly aided with direct comparisons of costs by breast cancer stage across three cancer types (triple-negative, HER2-positive, HER2-negative).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations